The English Language Teachers in Iraq Face Challenges and Have Opportunities Beyond Just Giving Knowledge - Zanyar Nathir Ghafar (International Journal Labs, 2023)
Recently, there have been some significant shifts in teacher education, which has resulted in a reorientation of attention away from transmitting designs and toward alternative models and techniques. These alternative methods and speculations surfaced in the post-transmission period and addressed socially constructed, diplomatic, philosophical, and essential careers. Even though teacher training programs have changed across the board, alternate theories and viewpoints seem to have little to no impact on Iraq's English language teaching (ELT) education agendas. This research examined the issues and difficulties experienced by instructors and educators working in Iraqi academic settings and the relevance of post-transmission viewpoints and theories to that situation. The data were gathered from the opinions and convictions of 8 knowledgeable English instructors, and three teachers were interviewed. The following data collection methods were used: collaborative discussion, reflective narration, and interviews. The data were captured so that new topics relevant to the current educational development in Iraq might be discovered. These topics included barriers, restrictions, and worries in the event of any reform. According to the study's findings, participants believed that educators, instructors, and decision-makers must accept many ideas and techniques to improve what was before and also in English as a foreign language in the Iraqi curriculum for teachers.